International broadcasting and its contested role in Australian statecraft : middle power, smart power - Heriot, Geoff (Anthem studies in soft power and public diplomacy., 2023)
An insightful and timely reappraisal of international broadcasting as an instrument of discursive rather than 'soft' power and its contested role in Australia's Indo-Pacific regional statecraft.--